AN ANALYSIS OF THE BUSINESS FEASIBILITY STUDY OF KOPIEMAS COFFE SHOP IN BANDUNG - Aulia, Amar Ali; Muhammad, Raji Rahma (Finansha: Journal of Sharia Financial Management, 2025)
This study aims to conduct a comprehensive feasibility analysis of Kedai Kopiemas, a micro and small enterprise located in Bandung, by evaluating marketing, production, human resource management, financial performance, and strategic (SWOT) aspects. The rapid growth of coffee shop businesses in urban areas underscores the need for an integrated feasibility assessment to ensure sustainability, particularly in financial and managerial dimensions. Using a descriptive analytical approach, this study combines qualitative data obtained from interviews and observations with quantitative data derived from financial records. The findings indicate that Kopiemas is highly feasible to operate and develop. Financial indicators show a positive Net Present Value (NPV) of IDR 41,784,810.77 (discount rate 16%) and an Internal Rate of Return (IRR) exceeding 20%, both of which confirm strong investment viability. Non-financial aspects further support this conclusion: the business benefits from an efficient competency-based HR structure and competitive strengths identified through SWOT analysis. This study contributes to MSME feasibility literature by offering an integrated assessment model that incorporates sharia-based sustainability principles, emphasizing the alignment between financial viability, ethical management, and community welfare.